Peningkatan Efisiensi Pengelolaan Stok Barang Melalui Aplikasi Berbasis Web di CV Bina Anak Papua - Isak Boas Samanui; Gunawan Prayitno (Jurnal Teknologi dan Informatika, 2024)
This community service activity aims to enhance the efficiency of stock management at CV Bina Anak Papua through the development and implementation of a web-based application. The current manual system is prone to errors, data inconsistencies, and inefficient inventory tracking. The proposed web-based application will streamline stock management processes, enabling real-time stock monitoring, automated reorder calculations, and comprehensive reporting. The project involves analyzing the current stock management practices, designing and developing the web application, providing staff training, and evaluating the application's impact on operational efficiency. Expected outcomes include reduced stockouts and overstocking, improved data accuracy, and enhanced decision-making capabilities for stock management. By leveraging web technology, this project aims to boost the competitiveness and productivity of CV Bina Anak Papua, ultimately contributing to the company's growth and sustainability.